Tehnološka navodila za izvedbo nekaterih ukrepov v pridelavi hrušk in češenj - Unuk, Tatjana; Lešnik, Mario; Rozman, Črtomir; Hudina, Metka; Stopar, Matej; Zlatić, Emil; Donik Purgaj, Biserka; Mrzlič, Davor; Tojnko, Stanislav (University of Maribor Press, 2018)
Manual for the Implementation of Selected Technological Measures for the Production of Pears and Cherries. A manual for the implementation of selected technological measures for pear and cherry production was created within the CRP 1409 - Technology of pears and cherry production project, financed by the Ministry of Agriculture, Forestry and Food of the Republic of Slovenia and the Slovenian Research Agency. The participants in the project were the University of Maribor - Faculty of Agriculture and Life sciences, University of Ljubljana - Biotechnical Faculty, Agricultural Institute of Slovenia, Institute for Agriculture and Forestry Maribor – Fruit growing Center Maribor and the Institute for Agriculture and Forestry Nova Gorica – Fruit growing Center Bilje. The content of the manual includes instructions for pear and cherry production, which were almost remowed from intensive production in the past, because of C. pyri and cherry rot problems, irrigation and nutrition issues, issues related to fruit set, and and measures related to postharvest treatments of fruit. The manual offers economically evaluated technological solutions for the implementation of key technological measures for the production of pears and cherries, which will enable the re-expansion of the production of these fruit species.